Textile Characteristics, Medullation, and Colorimetry of Wool Fiber Dyed with Dactylopius coccus Using Atmospheric Pressure Plasma Jet (APPJ) - Arturo Quispe-Quispe; Franklin Lozano; Virgilio Machaca-Machaca; Justiniano Quispe-Marcatoma (Applied Sciences)
The industrial and artisanal textile industries necessitate the adoption of sustainable dyeing practices. Although the natural dye derived from Dactylopius coccus presents a viable option, its traditional application requires metallic mordants that pose environmental and health risks. This study investigates the utilization of atmospheric-pressure plasma jet (APPJ) technology for dyeing wool with Dactylopius coccus dye, with the objective of optimizing the process and minimizing its environmental impact. The APPJ technique was employed for wool dyed with Dactylopius coccus dye, and the textile properties, medullation, and colorimetry were evaluated using an optical fiber diameter analyzer (OFDA) and a spectrometer with an integrating sphere. The results demonstrated that the APPJ enhanced the color intensity and uniformity, facilitating improved dye penetration into the fibers. Plasma treatment darkened the fiber, generated reddish and yellowish tones, and increased the color saturation and intensity. The wool samples treated with plasma exhibited an increase in DMF and SF but a decrease in IC and greater size variability. The APPJ reduces total medullation in wool dyed with cochineal dye. In conclusion, the APPJ was demonstrated to be a promising method for dyeing wool with Dactylopius coccus dye, offering an effective and sustainable alternative to traditional methods, with enhanced color vibrancy and uniformity and reduced resource utilization.